Association of multispecific CD4(+) response to hepatitis C and severity of recurrence after liver transplantation - Rosen, H R; Hinrichs, D J; Gretch, D R; Koziel, M J; Chou, S; Houghton, M; Rabkin, J; Corless, C L; Bouwer, H G (Gastroenterology (New York, N.Y. 1943), 1999)
After liver transplantation for hepatitis C virus (HCV), reinfection of the allograft invariably occurs. Indirect evidence suggests that the cellular immune response may play a central role. The purpose of this analysis was to determine the correlation between HCV-specific peripheral CD4(+) T-cell responses and the severity of recurrence after liver transplantation. Fifty-eight HCV-seropositive patients, including 43 liver transplant recipients with at least 1 year of histological follow-up, were studied. Peripheral blood mononuclear cells (PBMCs) were isolated from fresh heparinized blood and stimulated with either recombinant HCV antigens (core, E2, NS3, NS4, and NS5) or control antigens. Fourteen (40%) of 35 patients with mild or no evidence of histological recurrence within their allografts responded to at least 1 of the HCV antigens. Eleven responded to NS3, 5 to all the nonstructural antigens, and 3 to the HCV core polypeptide alone. In contrast, in the 8 patients with severe HCV recurrence, no proliferation in response to any of the HCV antigens was seen (P = 0. 03) despite responses to the control antigens. Despite immunosuppression, HCV-specific, major histocompatibility complex class II- restricted CD4(+) T-cell responses are detectable in patients with minimal histological recurrence after liver transplantation. In contrast, PBMCs from patients with severe HCV recurrence, despite being able to proliferate in response to non-HCV antigens, fail to respond to the HCV antigens. These findings suggest that the inability to generate virus-specific T-cell responses plays a contributory role in the pathogenesis of HCV-related graft injury after liver transplantation. It is hoped that further characterization of the immunoregulatory mechanisms related to recurrent HCV will provide the rationale for novel therapeutic strategies and diminish the incidence of inevitable graft loss.